2004
DOI: 10.1183/09031936.04.00063003
|View full text |Cite
|
Sign up to set email alerts
|

Safety of research bronchoscopy, biopsy and bronchoalveolar lavage in asthma

Abstract: Bronchoscopy with endobronchial biopsy (EBB) and/or bronchoalveolar lavage (BAL) has become an important research tool in asthma. A recent report has suggested audit and reporting of the safety of these procedures.A total of 159 asthmatic patients (84 males, 75 females), aged 18-52 (median 27) yrs, forced expiratory volume in one second 53-120 (median 88) % predicted, underwent 273 bronchoscopies in six clinical research studies. On 228 occasions, EBB and BAL were performed and, on 45 occasions, EBB was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 20 publications
3
39
1
5
Order By: Relevance
“…Most adverse effects observed in asthma patients submitted to bronchial thermoplasty are usually seen after bronchoscopic procedures. (18)(19)(20) In this case, there were no significant complications. After each of the three sessions of treatment, the patient was monitored in the recovery room.…”
Section: Case Reportmentioning
confidence: 77%
“…Most adverse effects observed in asthma patients submitted to bronchial thermoplasty are usually seen after bronchoscopic procedures. (18)(19)(20) In this case, there were no significant complications. After each of the three sessions of treatment, the patient was monitored in the recovery room.…”
Section: Case Reportmentioning
confidence: 77%
“…The predictive factors used to identify asthmatic patients with high bronchospasm risk during the procedure are: high bronchial hyperactivity, basal FEV 1 <60% than the theoretical value, unstable asthma with frequent bronchial crises and relevant symptoms, patients who suffer from asthma or who had previously undergone treatment in an Intensive Care Unit owing to bronchospastic crises [21] (Level of evidence: IV).…”
Section: Bronchial Asthmamentioning
confidence: 99%
“…A number of reports have suggested that bronchoscopy, including BAL and bronchial forceps and brush biopsy, can be safely performed for research purposes in patients with asthma and COPD (34,(71)(72)(73)(74). Repeated procedures have also been reported to be safe, at least in patients with mild asthma (59).…”
Section: Safetymentioning
confidence: 99%
“…Because concepts of asthma pathophysiology and inflammation in adults cannot be extrapolated to children (74,88,89), research fiberoptic bronchoscopy in combination with bronchoprovocation has been recently extended to children and adolescents. However, only a limited understanding exists about the underlying pathology of wheezing phenotypes in children (90).…”
Section: Bronchoprovocation and Research Bronchoscopy In Children: Apmentioning
confidence: 99%